Practicing the Sublime, Raising the Marginal Self: The Chinese Muslim Writer Zhang Chengzhi's Narrative of Adventure - Dang, Xiayin (Archīum Ateneo, 2024)
This paper examines the concept of “adventure” in a series of stories by a well-known Chinese Muslim writer Zhang Chengzhi (b. 1948). Zhang is famous for searching out and depicting landscapes, especially in northwest China. This paper will explore in what ways adventures in landscapes become a crucial mechanism for advancing plot development. How do adventures in Zhang’s stories create grand space-time in novels through transformations of different geographic topographies and historical moments? Why are these adventures depicted with attributes of the sublime? More importantly, what is the intertextual relationship between the adventures of the characters in the text and Zhang’s journey outside the text (i.e., in real life)? How does the space of adventures interplay between life and crisis for both the characters and writer? This study argues that in adventure stories, Zhang constructs a pattern of integration between the Jahriyya Muslims’ daily lives and their transcendent pursuits and a pattern of self-development and self-sublimation by virtue of telling adventure stories. Adventure is the allegorical device for both Zhang and the characters to practice the sublime—to achieve and reveal their physical and spiritual strength and ethnic characteristics. As such, this paper further asks in what ways the narrative of such a personal bildungsroman is intertextually identified with the subaltern community of Jahriyya Muslims, both within and outside the texts in the context of Han-centered Chinese culture.